2001
DOI: 10.1016/s0141-0229(01)00380-5
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic upgrade of old paperboard containers

Abstract: The use of enzymes in secondary fiber (old paperboard containers) upgrading was investigated. The following aspects were analyzed: (i) the effect of several enzymes and (non-hydrolytic) cellulose-binding domains on the pulp and paper properties; (ii) factors influencing enzymatic treatment of secondary fiber: enzyme dosage and reaction time; and (iii) enzyme action on fractions with different fiber-length.In general, all the tested enzymatic preparations were able to improve the pulp drainability. In most case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 6 publications
1
48
0
Order By: Relevance
“…Drainage rate of pulp of CBD-modified cellulose decreases compared with that of unmodified cellulose fibres [18]. This is consistent with the reduction of inter-surface repulsion, which results in fibre agglomeration and reduction of the drainability.…”
Section: Interaction Of the Surfaces Of Cellulose Modified By Cbdsupporting
confidence: 77%
See 1 more Smart Citation
“…Drainage rate of pulp of CBD-modified cellulose decreases compared with that of unmodified cellulose fibres [18]. This is consistent with the reduction of inter-surface repulsion, which results in fibre agglomeration and reduction of the drainability.…”
Section: Interaction Of the Surfaces Of Cellulose Modified By Cbdsupporting
confidence: 77%
“…For example, CBD, showing non-hydrolytic disruptive activity on cellulose fibers, causes a release of microfibrils as small particles and prevents the flocculation of microcrystalline bacterial cellulose [15][16][17][18]. These improve processability of the cellulose fibers and paper strength.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work (Pala et al, 2001), it was shown that although being very efficient for drainage improvement, enzymatic preparations such as Celluclast could be detrimental to paper strength.…”
Section: Resultsmentioning
confidence: 99%
“…The protein amount (94 mg/ml) was determined by the Bradford method, using serum albumin as standard (Bradford, 1976). Total cellulase (57 FPU/ml), Endoglucanase (26 U/ml) and Xylanase (680 U/ml) activities were measured by the filter paper, carboxymethylcellulase, and the xylan oat-spelt assays, respectively (Pala et al, 2001). Released sugars were measured by the dinitrosalicylic acid method, using glucose as standard (Bernfeld, 1955).…”
Section: Enzymementioning
confidence: 99%
“…Reducing sugar released during enzymatic hydrolysis was determined using the DNS method at a wavelength of 540 nm (Pala et al 2001). Reducing sugar yield (RSY) was calculated using Eq.…”
Section: Chemical Analysismentioning
confidence: 99%